Radiographic Features and Treatment Strategies of Impacted Maxillary Canines - Sefa Çolak; Nihat Akbulut; Halenur Altan; Ahmet Altan (Cumhuriyet Dental Journal, 2020)
Objective: Treatment of impacted maxillary canines is essential, both aesthetically and functionally. This study aims to define the radiographic features of maxillary impacted canines, evaluate treatment options, and to detect related pathologies.Materials and Methods: In this retrospective study, orthopantomographs, treatment options, and demographic features of the patients were analyzed. Impacted maxillary canines were classified according to the study of Yamamoto et al. According to this classification, maxillary canines are evaluated under seven types according to the occlusal plane and their relative location to adjacent teeth. Moreover, the pathologies around impacted canines were detected via panoramic radiographies.Results: 323 impacted maxillary canines of 270 patients were analyzed. Two hundred fifteen of these teeth (66.6%) belonged to females, while the rest 108 (33.4%) belonged to males. It was observed that impacted maxillary canines were bilateral in 53 patients and unilateral in 217 patients. In the classification based on direction and position of impacted maxillary canines, the highest rates was Type 2 (55.42%) which was followed by Type 4 (26.93%), Type 1 (12.38%), Type 7 (2.79%), Type 3 (1.86%) and Type 5 (0.62%), respectively. Twenty-eight patients with cystic lesion related to impacted maxillary canines were detected. Impacted maxillary canines concomitant with odontoma was detected in 4 patients. In 52 of the patients, it was detected that maxilla was edentulous except for the impacted canines, and the extractions of impacted canine teeth were due to prosthetic reasons. Thirty impacted maxillary canines of 24 patients (n=30, 9.28%) were placed buttons for orthodontic maintenance, while surgical tooth extraction was preferred as a treatment option in other patients.Conclusions: Orthodontic, surgical treatments or combinations may be preferred depending on the impact level of the canine. Early diagnosis and correct orientation of the patient is essential for the success of the treatment.